The Dynamics and Water Quality Status of a Tropical Coastal Lake in Anak Laut Lake, Singkil Indonesia - Leidonald, Rusdi; Muhtadi, Ahmad Muhtadi; Susetya, Ipanna Enggar; Dewinta, Astrid Fauzia; Hasibuan, Julia Syahriani; Simamora, Lauran F.M.; Saville, Ramadhona (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Anak Laut Lake a tropical coastal lake in Singkil, Aceh Province, is directly connected to the Indian Ocean on the northwestern part of Sumatra Island. The existence of oil palm plantations in the northern part of Lake Anak Laut has the potential to pollute the lake waters. Therefore, this research aims to determine the dynamics of water quality which is influenced by the tidal cycle and the level of pollution of Lake Anak Laut. This research was conducted on March and April 2023. Water sampling was conducted in four (4) times, following the tidal cycle, namely new month, first quarter, full moon, and last quarter. The sampling was also carried out at high and low tides. The method for determining water pollution is the Canadian Council of Ministers of the Environment (CCME) and Pollution Index Method (PI). The results of the research show that the current and water level of Anak Laut Lake varies according to the tidal cycle, so the water quality fluctuates greatly following the tidal cycle. The concentration of organic matter and nutrients as well as Total Coliform showed higher in the last quarter phase where the water entering the lake was very low. The high level of organic matter is caused by 'waste' from palm oil plantation activities located north of Anak Laut Lake. The water quality status of Anak Laut Lake is categorized as marginal-poor based on CCME (score 42-66) and moderate based on PI (score 5-8). In general, water quality conditions are "better" at high tide (new month and full moon) than at low tide (first quarter and last quarter).